Two cities: between representations and produced images - Sassi Boudemagh, Souad (2008)
There is a tendency within literature and scientists thoughts related to urban researches that says there is no crisis of the reality of the city, but there is a crisis of the representation of this reality. Could the image of a city cancel the city itself? Despite the fact that it is hard to figure out something while it is still taking form; this paper explains, to some extent, the close tie between the image of a city and its representation. The two cities we speak about are Constantine city and the new town of Ali Mendjelli. They are in opposition, a bit paradoxical, as well in the remarks that represent the inhabitants’ feelings as in the specialists' thoughts: “the ancient city and the new city ". A frequent mobility from one city to another constitutes an actual parameter associated to a field of possibilities which makes it likely to socially institute an individual capacity of selection and comparison, even evaluation, and social criticism. To understand inhabitants reaction as well as his mode of adaptation, while his mobility between the two different environments, as sense producing urban entities, we will give insights in points that are relevant to the identity of a city, with a focus on the impact of a rapid urbanization beside an age-old one on citizen mental images. Keywords: Age-old city, Rapid urbanization, Built landscape features, Mental representations, Identity, Visual culture, Space appropriation.